Rancang Bangun Musik Tradisional Minangkabau Berbasis Immersive Technology - Jelita Kristin Sagala; Fris Okta Falma (Lembaga Yasin AlSys, 2026)
Although the use of immersive technology to introduce cultural heritage continues to develop, media integrating the forms, sounds, and simulated performance of traditional Minangkabau musical instruments remain limited. This study aimed to design and develop an immersive technology-based Minangkabau traditional music application as an interactive medium for cultural introduction. The study employed a research and development approach using the Multimedia Development Life Cycle model, which comprises the concept, design, material collecting, assembly, testing, and distribution stages. The data sources included traditional musical instruments, scientific documents, and one purposively selected Minangkabau music practitioner. Data were collected through observation, semi-structured interviews, a literature review, documentation, and functional testing, and were subsequently analyzed descriptively using SWOT analysis. The result of the study was a Windows-based virtual reality application featuring three-dimensional models of talempong, canang, and gandang katindiak, along with recordings of the original instrument sounds. The implementation of a collider system, virtual reality controllers, a touch-detection script, and Audio Source enabled users to play the instruments using both hands, including producing the distinct “dum” and “tak” sounds of the gandang katindiak. Internal testing indicated that the navigation functions, object responses, and audio output operated according to the design. These findings extend the use of immersive technology as an interactive medium for introducing and preserving traditional Minangkabau music. However, the application’s effectiveness in improving users’ understanding of and interest in Minangkabau culture still requires testing with broader user groups.